THE USE OF ENGLISH ON ONLINE MEDIA (WHATSAPP BROADCAST) IN FRONT OFFICE DEPARTMENT AT GALERI CIUMBULEUIT HOTEL - Murtala, Alifah A.; Thamrin, Husni; Alwasilah, Senny S.; Maulana, Angga (IPI Garut Press, 2021)
Hotel is one of the places that people choose to spend their time while on vacation or in the context of business. Each hotel certainly has its own way of attracting people to come to their hotel to stay and come back later. Galeri Ciumbuleuit Hotel is one of the hotels that has a unique way of conveying information, especially regarding hotel promos to guests. They use online media (Whatsapp Broadcast) to provide information about hotel promos. Of course they have their own way of sending broadcast messages. They definitely choose a certain style of language to attract customers. As will be discussed in this study,